FUNDAMENTALS OF THE ARTISTIC WORLD VIEW IN THE LYRICS OF NODIRA (Scientific journal of the Fergana State University, 2023)
This article is devoted to the study of the lyrics of Nodira in order to show that the genesis of the foundations of the artistic worldview is based on religious and educational, philosophical and mystical issues. The article reveals the influence of religious, educational, philosophical and mystical ideas on the emergence of Nodira's poetry on the example of her poems.